Ti–Mn hydrogen storage alloys: from properties to applications. Issue 55 (14th December 2022) - Liu, Jianjun; Sun, Lei; Yang, Jinggang; Guo, Dongliang; Chen, Dabing; Yang, Liheng; Xiao, Peng
Abstract : The hydrogen storage properties, regulation methods and applications of Ti–Mn hydrogen storage alloys were reviewed. Abstract : Efficient and safe storage of hydrogen is an important link in the process of hydrogen energy utilization. Hydrogen storage with hydrogen storage materials as the medium has the characteristics of high volumetric hydrogen storage density and good safety. Among many hydrogen storage materials, only rare earth-based and titanium-based hydrogen storage alloys have been applied thus far. In this work, current state-of-the-art research and applications of Ti–Mn hydrogen storage alloys are reviewed. Firstly, the hydrogen storage properties and regulation methods of binary to multicomponent Ti–Mn alloys are introduced. Then, the applications of Ti–Mn alloys in hydrogen storage, hydrogen compression and catalysis are discussed. Finally, the future research and development of Ti–Mn hydrogen storage alloys is proposed.